Pembagian Harta Warisan Sebelum Orang Tua Meninggal: Studi Kasus Masyarakat Muslim Kecamatan Medan Tembung - Heriandi Heriandi; Zainul Aziz Nasution; Akmaluddin Syahputra; Iwan Iwan (TADHKIRAH: Jurnal Terapan Hukum Islam dan Kajian Filsafat Syariah, 2025)
This study discusses the practice of inheritance distribution before the parents' death among the Muslim community in Medan Tembung District. This phenomenon reflects the dynamic interplay between Islamic law, customary law, and social practices in the division of inheritance. According to Islamic law, inheritance can only be distributed after the death of the testator. However, in Medan Tembung, early distribution is often carried out to avoid conflicts among heirs. This research uses a socio-legal approach with an empirical method based on field observations. The findings show that the community applies three inheritance systems: individual, matrilineal, and parental/bilateral. The distribution is conducted through hibah (grants) or wasiat (wills), typically documented in a written statement and often legalized by local community leaders or notaries. Cultural factors, education levels, and legal awareness significantly influence the variation in distribution systems. Most families still distinguish between the inheritance shares of sons and daughters, with sons typically receiving a larger portion. Community leaders play a vital role in mediating disputes, and if consensus is not reached, legal channels are pursued. These findings highlight the importance of legal education and the need for synergy among religious law, customary practices, and state law to ensure fairness in inheritance distribution.